Antifungal susceptibility pattern of Candida species isolated from pregnant women - Ali, Maqsood; Edrees, Wadhah Hassan; Al-Shehari, Wadee Abdullah; Xue, Gao; Al-Hammadi, Safa; Qasem, Eglal Ahmed; Chaulagain, Ram Prasad; Lal, Nand (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionCandida species, opportunistic yeast, are the second most common cause of female vulvovaginal candidiasis. This study aimed to evaluate the antifungal susceptibility profile of the isolated Candida species in pregnant women in Hajjah governorate, Yemen.MethodsA hospital-based cross-sectional study was conducted among 396 pregnant women attending Authority AL-Gumhorri Hospital Hajjah between February and July 2023. Vaginal swabs were collected, and Candida species were isolated and identified based on the standard laboratory method. Furthermore, the antifungal drug susceptibility of Candida species was determined by the Kirby-Bauer technique.Results and discussionThe prevalence of vaginal Candida infection among pregnant women was 61.4%. Candida albicans was the most predominant species (59.26%), followed by Candida krusei(13.58%), Candida Tropicalis (11.12%), Candida Grabata (9.87%), and Candida dubliniensis (6.17%). The highest rate of Candida infections was among women aged 24–30 years (71.9%) who finished primary school (77.8%), with the third trimester (80%), multigravida (66.1%), and recurrent infection (67.7%) showing significant differences (P < 0.05). The Candida albicans isolates were resistant to clotrimazole and itraconazole at 34.7% and 23.6%, respectively.In addition, the resistance of Candida krusei, Candida tropicalis, Candida glabrata, and Candida dublinensis isolates to fluconazole, voriconazole, voriconazole, and nystatin was 57.6%, 63%, 43.8%, and 60%, respectively. Additionally, approximately 46.2% of isolated Candida albicans exhibited one kind of antifungal drug resistance, whereas 38.7% of isolated non-albicans exhibited resistance to three different antifungal agents. According to the above findings, Candida infection is highly prevalent in Yemen and quite widespread. Interventions in health education are advised to increase women’s knowledge of vaginitis and its prevention. The antifungal susceptibility test may also be helpful in determining the best medication for each patient.